Cardiovascular Control during Exercise in Type 2 Diabetes Mellitus - Simon Green; Mikel Egaña; J. Chris Baldi; Regis Lamberts; Judith G. Regensteiner (Journal of Diabetes Research)
Controlled studies of male and female subjects with type 2 diabetes mellitus (DM) of short duration (~3–5 years) show that DM reduces peak V˙O2 (L·min−1 and mL·kg−1·min−1) by an average of 12–15% and induces a greater slowing of the dynamic response of pulmonary V˙O2 during submaximal exercise. These effects occur in individuals less than 60 years of age but are reduced or absent in older males and are consistently associated with significant increases in the exercise pressor response despite normal resting blood pressure. This exaggerated pressor response, evidence of exertional hypertension in DM, is manifest during moderate submaximal exercise and coincides with a more constrained vasodilation in contracting muscles. Maximum vasodilation during contractions involving single muscle groups is reduced by DM, and the dynamic response of vasodilation during submaximal contractions is slowed. Such vascular constraint most likely contributes to exertional hypertension, impairs dynamic and peak V˙O2 responses, and reduces exercise tolerance. There is a need to establish the effect of DM on dynamic aspects of vascular control in skeletal muscle during whole-body exercise and to clarify contributions of altered cardiovascular control and increased arterial stiffness to exertional hypertension.